Governmental Capacity and Statehood in the Autonomous Region in Muslim Mindanao - Anfilova Natalia Vladimirovna (JURNAL VENUS, 2018)
During the process of achievement of autonomy through peaceful negotiation, started in the 1970s, such political formation as the Autonomous Region in Muslim Mindanao (ARMM) was established. Nevertheless, this process was accompanied by inner disturbances: clashes, popular unrest and terrorist attacks. The politically active part of the Moro people was divided into groups consisted of supporters of various measures - from moderately liberal to extremely radical. Although nowadays the Moro National Liberation Front (MNLF) 1 and Abu Sayyaf 2 represent diametrically opposed positions, since MNLF is a Philippine government‘s ally, while Abu Sayyaf is a terroristic group, they originated from common source and share the discontent around the existing order towards the Moro people in the Philippines. In spite of the fact that autonomy of ARMM was extended, the significant part of its Moro population is still seeking for an ultimate separation from the Philippines. On the one hand, decentralization and autonomy includes a number of benefits, e.g. , ―increased public sector efficiency, accountability, and effectiveness, increased citizen participation, local ownership, and durable peace‖ 3. On the other hand, an abrupt separation can lead to institutional disarray, economic decline, deterioration of social problems, and even anarchy, unless the separated territory is prepared to the self-government. In that context ―being prepared‖ implies conforming the criteria of the state (or approaching to them) and having corresponding own institutions to manage the political formation self-sufficiently. Depending on the approach of understanding of the state, the last condition can be included in its criteria.